The sparse decomposition of sound in the time domain using non-negative quadratic programming. - HOUGHTON, CONOR JAMES (My University, 2009)
Non-negative matrix deconvolution and sparse decomposition are useful tools for source separation and acoustic object recognition. Here, a new algorithm for calculating a sparse decomposition of sound in the time domain is derived using non-negative quadratic programming.
PUBLISHED
Keywords: Pure & Applied Mathematics